2011
DOI: 10.2495/fsi110061
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on a dry granular avalanche impacting an obstacle: dead zone, granular jump and induced forces

Abstract: This work describes small-scale laboratory tests on dry granular avalanches. Avalanches flow down a channel and impact a wall-like obstacle. A deposit generates upstream of the obstacle and plays an important role in the definition of the total mean force induced on the obstacle by the flow. The estimation of this force is crucial to design efficient protection structures against snow avalanches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Gray et al (2003) and Pudasaini et al (2007) showed that the granular jump increases rapidly in thickness after impact and propagates upslope, similarly to pure fluid flows (Savage and Hutter 1989). Gray et al (2003), and later Tiberghien et al (2007), and Caccamo et al (2011Caccamo et al ( , 2012, showed that a granular jump can evolve into a basal stagnation zone (i.e., where the granular material is static) overlain by the flowing material, which overtops the obstacle. Our experimental flows with Froude numbers of 3-5 were prone to granular jump.…”
Section: Flow Interaction With the Channel Bendmentioning
confidence: 80%
“…Gray et al (2003) and Pudasaini et al (2007) showed that the granular jump increases rapidly in thickness after impact and propagates upslope, similarly to pure fluid flows (Savage and Hutter 1989). Gray et al (2003), and later Tiberghien et al (2007), and Caccamo et al (2011Caccamo et al ( , 2012, showed that a granular jump can evolve into a basal stagnation zone (i.e., where the granular material is static) overlain by the flowing material, which overtops the obstacle. Our experimental flows with Froude numbers of 3-5 were prone to granular jump.…”
Section: Flow Interaction With the Channel Bendmentioning
confidence: 80%
“…1. We do not consider the avalanche front but only the avalanche body and tail when the stagnant zone is formed (constant length L over time while trueu¯ and h can change over time, as reported in Caccamo et al [2011]): the dead zone angle α dz is equal to the steady value defined by α dz = θ − θ min , as described by Chanut et al [2010]. θ min is the angle associated with quasi‐static deformations, i.e., the minimum angle above which steady flows can occur (as is defined by Pouliquen [1999]).…”
Section: A Scaling Lawmentioning
confidence: 99%
“…The cross‐comparison of H / h and H c / h in Figure 1 shows that granular bores are expected to be formed at very short times ( H > H c for t < t 1 : first impact of the dilute avalanche front) and at final times just before the avalanche comes to rest ( t > t 2 ) while a dead zone process is likely to occur during most of the time of the flow‐wall interaction ( H < H c for t 1 < t < t 2 ). A detailed experimental analysis of the transition at time t 2 was provided by Caccamo et al [2011] and demonstrated that this analysis was relevant and promising. Investigating the transition at time t 2 from a dead zone process (solid‐like, stagnant zone that co‐exists with a fluid‐like, inertial zone above) towards a granular jump remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%